A STUDY ON POLITENESS STRATEGIES OF CHARACTERS IN THE BIG WEDDING MOVIE DIRECTED BY JUSTIN ZACKHAM - Ferdianita Lucky Nur Safitri (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2015)
In every place have some unwritten rules depend on the countries, beside people use a language, they use a politeness also. Politeness is important thing that people must know when they communicate with other people and make a polite conversation. Politeness strategies are used to formulate messages in order to save hearer’s face when face-threatening acts are invitable or desire. Brown and Levinson stated four main types of politeness strategies: bald on-record, positive politeness, negative politeness, and off-record (indirect). In this study is intended to analyze politeness strategies that used by characters in “The Big Wedding Movie”. There is a problem that is discussed in this study (1) what politeness strategies are used on “The Big Wedding Movie”? (2) why do characters in “The Big Wedding Movie” use politeness strategies? This analysis focus on the politeness strategies that used by characters in the conversation of “The Big Wedding Movie”. The researcher applied the qualitative research and used descriptive methods in this study because all data are in the form of words. Meanwhile, the type of the research is content analysis because it intended to analyze the content of the data which are in the form of movie script to find the politeness stretegies. When analyze the data, the researcher used the theory of Brown and Levinson about politeness strategies. Based on the result of the analysis, it is found that there are eighty six utterances that use four politeness strategies. They are bald on-record with twenty nine utterances, positive politeness with thirty eight utterances, negative politeness with ten utterances, and off-record with twelve utterances. The most frequently used politeness is positive politeness, bald on-record, off-record, and the less frequently used is negative politeness. For supporting the study, the researcher needed source of the theories related to politeness strategies such as : bald on-record, positive politeness, negative politeness, and off-record (indirect). From the findings, the researcher expected that the result of this study will useful for English learners to get the information from politeness strategies found in the movie of “The Big Wedding Movie”.